Propofol-medetomidine-ketamine total intravenous anaesthesia in thiafentanil-medetomidine immobilised impala (Aepyceros melampus) - Zeiler, Gareth Edward (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.